Exploring the Needs of Lecturers for Blended Project-Based Learning in Argumentative Writing - Elfi Elfi; M. Zaim; Refnaldi Refnaldi; Fauzul Aufa (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2024)
The Blended Project-Based Learning (BPjBL) model plays a crucial role in enhancing argumentative writing skills. To implement this model, it is essential to conduct a needs analysis with lecturers. It helps identify their specific requirements and preferences in developing and applying the model.The study aimed to explore lecturers' need for the necessity aspect of the BPjBL model in teaching argumentative writing. The design of the research was quantitative by using a survey. The respondents of the research were 15 lecturers from various universities in Indonesia. They have been chosen using a purposive sampling technique. The criteria were the lecturers who had taught argumentative writing at the university.  The data was collected through a questionnaire. The questionnaire was validated by two experts, and the result was very valid. The reliability of the questionnaire was excellent, with a mean score of 0.964. The study was analyzed by using descriptive analysis statistics using SPSS 38. From this study, it was found that the lecturer highly needed the aspects of argumentative writing reason, argumentative writing topic, argumentative writing skill, language ability, language structure, language use, argumentative writing context, and teaching model with a mean score of 3.33. The findings showed that lecturers are highly needed for the argumentative writing aspect and teaching models such as blended learning and project-based learning.